The Revival of Cholera Vaccines: The Century-Old Making of a Global Success Story - Heyerdahl, Leonardo (Anthropologica, 2024)
Cholera vaccines have existed since the nineteenth century but were largely considered an ineffective control strategy for much of their history. However, in 2012, cholera vaccination campaigns were piloted in Haiti and Guinea using a preexisting vaccine formula. These initial efforts quickly expanded to dozens of countries. A global stockpile of millions of doses was established, positioning cholera vaccines as a cornerstone to the Global Task Force on Cholera Control’s Roadmap to ending cholera by 2030. What factors contributed to this remarkable turnaround? This piece explores the epistemic, moral, and industrial reconfigurations that sustained the crafting of a global vaccine success story and its ramifications within a shifting global health landscape, including the potential displacement of water and sanitation interventions. The research is based on my participation in cholera vaccine introductions as a medical NGO worker and on symmetric ethnographic fieldwork conducted in African settings targeted for reactive cholera vaccination and in global North centers influencing global cholera vaccine policy.